PEMANFAATAN JERAMI NANGKA (Artocarpus heterophyllus) SEBAGAI BAHAN BAKU YOGHURT NANGKA - N. Winarsih; Tatang Sopandi (FMIPA : Universitas PGRI Adi Buana, 2014)
Has done research on the utilization of straw jackfruit (Artocarpus heterophyllus) as a raw material jackfruit yogurt. The study was conducted using 400 g straw jackfruit divided into 4 treatment groups of each 100 g. Each treatment group was added water with straw comparison with water 1:3, 1:4, 1:5, and 1:6 in order to obtain the concentration in the medium straw jackfruit 333, 250, 200, and 170 g / l. Furthermore, from each treatment group divided by 5 as replication. After fermentation for 72 hours with a temperature of 28-30 º C, analyzed the number of bacteria, nitrogen, carbon, glucose, viscosity and assessment of sensory characteristics (odor, taste and color) jackfruit yogurt straw. The results showed that the use of straw as a raw material jackfruit yogurt affect the amount of bacteria, nitrogen, carbon, glucose and viscosity but had no significant effect (P < 0.05) on sensory characteristics (odor, taste and color) yogurt. Keywords: straw jack fruit, yoghurt